Quality of Life related to health in the morbidity of periodic hemodialysis patient - Eliseo Capote Leyva; Milagros Ortiz González; Raydel Argudín Selier; Carmen Elena Viada González; Lázaro Capote Pereira; Idrissa Leonard Rupalé (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Foundation: chronic renal failure has a negative impact in the quality of life and constitutes a morbidity predictor in patients with periodic hemodialysis. Objective: to evaluate the influence of quality of life related to health in the morbidity of patients in intermittent periodic hemodialysis. Methods: a descriptive study was done in patients with three or more time of intermittent periodic hemodialysis at the Nephrology service of the Military Hospital Dr. Carlos J. Finlay. Havana, in a 12 month follow up period. The variables analyzed were: age, sex, time with the substituting renal function treatment, morbidity rate, type of morbidity in hemodialysis and hospital admission rate. A questionnaire for quality of life in patients with renal disease (version 1.3) was applied. Results: patients under 60 years old predominated, of high schooling level, with blood hypertension mainly due to renal failure.  The most frequent morbidities were: chills, arterial Hypotension, and complications related to vascular access. The admission rate was low. The summary physical component had the lower punctuation followed by the summary mental component. Among these and age there was found an inversely proportional correlation, so as the morbidity rate and the summary physical component. Conclusion: the results obtained are related to preceding studies. The physical component summary results with higher involvement, mainly in the older adult, considering the negative relation with the morbidity rate and hospital admission.